Ultra-Precise 40Ar/39Ar Geochronology: Development of 38Ar cosmogenic exposure and olivine (U-Th)/He dating techniques; and deciphering the geochemical evolution of the Newer Volcanic Province, SE Australia - Oostingh, Kornelia Fieneke (Curtin University, 2017)
In this study, existing (40Ar/39Ar) and underdeveloped (terrestrial cosmogenic 38Ar exposure dating and olivine (U-Th)/He dating) geochronology techniques are used and improved to better understand the igneous geology and landscape evolution of Australia. It is shown that an integral approach of geochemistry and ultra-precise geochronology, using the new generation multi-collector mass spectrometers, is of paramount importance to decipher the volcanic history of the small, intraplate Newer Volcanic Province in SE Australia.